An overview of prognostic markers in patients with CLL - Braish, Julie; Cerchione, Claudio; Ferrajoli, Alessandra (Frontiers in Oncology, 2024)
Chronic lymphocytic leukemia (CLL) is a low-grade B-cell lymphoproliferative disorder. It is the most prevalent type of leukemia in the western countries, with a median age at diagnosis of 70 years. In 2023, it is estimated that there will be 18,740 new cases of CLL, and an estimated 4,490 people will die of this disease. It represents 1.0% of all new cancer cases in the U.S. The rate of new cases was 4.6 per 100,000 men and women per year based on 2016-2020 cases, age-adjusted. Death rates from CLL are higher among older adults, or those 75 and older. The death rate was 1.1 per 100,000 men and women per year based on 2016-2020 deaths, age-adjusted. (1) A common question that patients with CLL ask during their first clinic visit is: "How long will it be before I would need treatment?" Although this might seem like a simple question, the answer is not straight forward.CLL is a heterogenous disease, with a variable clinical course. Some patients may present with an aggressive disease requiring early initiation of treatment, while others have an indolent course and some, having so called smoldering CLL, may never need treatment. The variability in disease course can make predicting disease prognosis a complicated process. This brings forth the importance of establishing prognostic models that can predict disease course, time to treatment, and survival outcomes in such a heterogenous disease. The Rai and Binet staging systems were developed in the late 1970s to early 1980s.(2, 3) They separated patients into different stages based on clinical characteristics and laboratory findings. These simple staging systems are still in use; however, several prognostic markers need to be added for an individualized assessment and, with the recent development of genomic techniques leading to better understanding of CLL at the molecular level, newer prognostic markers have emerged.(4)